2019
DOI: 10.1101/2019.12.16.861872
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Secreted microbial metabolites modulate gut immunity and inflammatory tone

Abstract: Bioactive 15Running title: Production of NF-κB suppressive bioactives by the human gut microbiota 16 Abstract 20Evidence is emerging that microbiome-immune system crosstalk regulates the tenor of host 21 intestinal immunity and predisposition to inflammatory bowel disease (IBD). We identified 22five NF-B suppressive strains affiliated with Clostridium clusters IV, XIVa and XV that 23 independently suppressed secretion of the chemokine IL-8 by peripheral blood mononuclear 24 cells and gut epithelial organoids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…The cell-free supernatant of Pseudoflavonifractor sp. AHG0008 showed the ability to suppress IL-8 secretion by peripheral blood mononuclear cells [43,44]. However, little was known about the role of Pseudoflavonifractor in the gastrointestinal sites.…”
Section: Discussionmentioning
confidence: 99%
“…The cell-free supernatant of Pseudoflavonifractor sp. AHG0008 showed the ability to suppress IL-8 secretion by peripheral blood mononuclear cells [43,44]. However, little was known about the role of Pseudoflavonifractor in the gastrointestinal sites.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from the same group showed similar results using 5 different human gut bacterial strains from the Clostridia genus, also isolated by metaparental mating. [ 21 ] Postbiotics derived from the isolated bacteria were able to suppress NF‐κB activation in a strain‐specific manner: they compared the suppressive capacity of bacterial isolates assigned to the same operational taxonomic units (≥97% 16S rRNA sequence identity) and found differences between species in their ability to repress NF‐κB activation—as also showed by others. [ 131 ] Going one step further, they also determined that the suppressive capacity of almost all the examined strains corresponded to the <3 kDa fraction of the postbiotics.…”
Section: Study Of Postbiotics’ Effects In In Vitro Models Of Intestinmentioning
confidence: 79%
“…demonstrated the usefulness of organoid culture for studying the anti‐inflammatory effects derived from bacterial postbiotics. [ 21 ]…”
Section: Study Of Postbiotics’ Effects In Ex Vivo Models Of Intestinamentioning
confidence: 99%
See 2 more Smart Citations